Standardization research in information technology new perspectives - Jakobs, Kai 1957-.; Gale Group (Hershey, Penn. Information Science Reference, 2008)
"This book amasses cutting-edge research on the application of standards in the market, covering topics such as corporate standardization, linguistic qualities of international standards, the role of individuals in standardization, and the development, use, application, and influence of information technology in standardization techniques"--Provided by publisher.
Challenges for formal standardization : the institutional reforms of 2008-2010 reconsidered / Ulrich Blum -- IT standardization : the billion dollar strategy / John Hurd, Jim Isaak -- Best practice in company standardization / Henk de Vries -- Open standards requirements / Ken Krechmer -- Thed role of individuals and social capital in POSIX standardization / Jim Isaak -- Linguistic qualities of international standards / Hans Teichmann, Henk de Vries, Albert Feilzer -- A diffusion model for communication standards in supply networks / Michael Schwind, Tim Stockheim, Kilian Weiss -- Scope and timing of deployment : moderators of organizational adoption of the Linux server platform / Joel West, Jason Dedrick -- Standards for business component markets : an analysis from three theoretical perspectives / Heiko Hahn, Klaus Turowski -- Should buyers try to shape IT-markets through non-market (collective) action? / Kai Reimers, Mingzhi Li -- Comparing the standards lens with other perspectives on IS innovations : the case of CPFR / M. Lynne Markus, Ulric J. Gelinas, Jr. -- Market response to ISO 9000 certification of software engineering processes / G. Keith Fuller, Ilan Vertinsky -- The value of Web design standards for mobile computing / Matt Germonprez, Michel Avital, Nikhil Srinivasan -- Developing country perspectives on software : intellectual property and open source : a case study of Microsoft and Linux in China / Xiaobai Shen -- Copras : encouraging ICT research projects to produce more tangible standardization results / Bart Brusse.
Electronic reproduction.
Keywords: Information technology -- Standards; Standardization; Electronic books